The use of microdialysis to characterize the endocrine production of human subcutaneous adipose tissue in vivo - Dostálová, Ivana; Kaválková, Petra; Haluzíková, Denisa; Housová, Jitka; Matoulek, Martin; Haluzík, Martin (Regulatory peptides, 2009)
OBJECTIVE: Adipose tissue-derived factors represent important players in the metabolic regulations acting both on systemic and local level. However, their local concentrations in human adipose tissue are poorly described. METHODS: We measured 24-hour profile and post-glucose load concentrations of selected adipokines in the subcutaneous adipose tissue of 17 healthy women by in vivo microdialysis. During 24-hour period, subjects consumed two standardized meals (at 13.00 h and at 19.00 h). RESULTS: During 24-hour period, fat interleukin-6, interleukin-8/CXCL8, resistin, and hepatocyte growth factor (HGF) exhibited increase/decrease/plateau pattern and peaked at about 14.30 h. Fat leptin exhibited increase/plateau/decrease/increase pattern and reached plateau between 22.00 and 5.30 h. Fat adiponectin exhibited decrease/plateau pattern and reached plateau between 1.00 and 7.00 h. Fat plasminogen activator inhibitor-1 (PAI-1) exhibited decrease/increase pattern with the lowest value at 20.30 h. Oral glucose consumption significantly increased fat adiponectin and resistin levels and decreased fat leptin and PAI-1 levels, respectively. CONCLUSIONS: The levels of studied adipokines in subcutaneous fat exhibited significant variations during the 24-hour period after microdialysis catheter insertion that were not reflected in the circulation. Concentrations of adiponectin, resistin, leptin and PAI-1 were regulated by oral glucose ingestion from 1 to 3 h after oral glucose load in healthy women.
Keywords: Resistin; Female; inhibitor aktivátoru plazminogenu 1; adiponektin; Interleukin-8; mladý dospělý; ženské pohlaví; Leptin; Plasminogen Activator Inhibitor 1; Adiponectin; lidé; adipokiny; podkožní tuk; Subcutaneous Fat; Interleukin-6; Microdialysis; Adipokines; mikrodialýza; interleukin-8; leptin; glukosa; Young Adult; Glucose; interleukin-6; resistin; Humans